Model of protection means of printed documents - Шевчук, Анатолій Васильович (Ukrainian Information Security Research Journal, 2013)
As of today, the number of protection means in regard to printed documents increases in order to minimize an unauthorized access to information on the tangible medium. There was a need for developing protection models in order to prevent counterfeiting. It was analyzed that the model of protection is formed under the influence of technological factors of document production, as well as combination of protection means and consumer characteristics of the printed document. It was shown that there are six factors influencing consumer characteristics: run length of the document, lifetime of the document, documents’ velocity of circulation, intensity of control, intensity of exchange and the available degree of printed document protection. Use of protection models shall make it possible to create the best protection tools for a specific document with its functional features, and calculate the system of effects on the documents’ protection levels.